Exploring the impacts of climate and policy changes on coastal community resilience: Simulating alternative future scenarios. (November 2018) - Mills, Alexis K.; Bolte, John P.; Ruggiero, Peter; Serafin, Katherine A.; Lipiec, Eva; Corcoran, Patrick; Stevenson, John; Zanocco, Chad; Lach, Denise
Abstract: Coupled models of coastal hazards, ecosystems, socioeconomics, and landscape management in conjunction with alternative scenario analysis provide tools that can allow decision-makers to explore effects of policy decisions under uncertain futures. Here, we describe the development and assessment of a set of model-based alternative future scenarios examining climate and population driven landscape dynamics for a coastal region in the U.S. Pacific Northwest. These scenarios incorporated coupled spatiotemporal models of climate and coastal hazards, population and development, and policy and assessed a variety of landscape metrics for each scenario. Coastal flooding and erosion were probabilistically simulated using 99 future 95-year climate scenarios. Five policy scenarios were iteratively co-developed by researchers and stakeholders in Tillamook County, Oregon. Results suggest that both climate change and management decisions have a significant impact across the landscape, and can potentially impact geographic regions at different magnitudes and timescales. Highlights: A framework for comparing adaptation policies under a range of climate impact scenarios is presented. Probabilistic simulation of total water levels capture coastal flooding and erosion hazards. Policy scenarios were co-developed with local stakeholders to represent a range of management strategies. Simulated future landscapes were compared using metrics related to development, property risk, and public good. Both climate change and management decisions have a significant impact across the coastal landscape.